“Quem dá as cartas, meu velho?”: um estudo sobre a proteção social na velhice - Francisco, Denise Aparecida (2022)
The objective of this dissertation is to analyze elderly people's trajectory in access to social security policies in the county of Vinhedo/SP. It was sought to deepen our knowledge in the ways through which aged workers relate themselves to programs, projects, services, and benefits, as to identify patterns in the social coverage of health, social security, and social assistance policies. Being inserted in the critical social gerontology field, this research has sought to analyze the impacts of the aging process on research subjects in a context of bourgeois sociability marked by social inequality, as well as demands in the field of social security. Defining the research universe through the local social protection system from the county of Vinhedo/SP, it was sought to create a representative sample of the population segment at stake, by selecting twelve elders whose trajectory is related to social security policies, currently or previously tied to these, mixing gender, race/ethnicity, and social classes, considering four users from each social policy, respectively. The central guiding hypothesis for this research consists of the question regarding the social protection embodiment, namely, if social security services guarantee conditions for an efficient exercise of the right to citizenship, or if they reveal themselves as excluding practices, making aging invisible in its class, gender, and race/ethnicity relationships, which aggravates social inequality. As to the methodological path, it was sought to, via bibliographical research, highlight tendencies regarding aging in the contemporary capitalist society, contributions in critical social gerontology, achievements in the social security field and setbacks in the context of neoliberal counter-reforms, the defense of social policy under the State's responsibility and pressure in favor of private sector interests, disputes around public funds, favoring financial capital, in detriment of social rights. By using documental research, it was sought to characterize the county of Vinhedo in its historical, economic, social, and cultural aspects, factors which are essential in understanding the social protection system in its local dimension, as well as identifying it through via its services, benefits and programs aimed at elderly people. The empirical research has favored the "place of speech" of elderly people as to their perspectives related to access; conceptions related to citizenship rights in the use of social security, health, and social assistance policies; expectations and challenges in the condition of elders who demand social protection, their perceptions in relation to aging and, at last, survival and resistance strategies adopted in the context of an unequal society. It was also resorted to semi-structured interviews with the twelve research subjects, collecting statements regarding their relationship with the offered services and their providers. The analyses have evinced the decisive character of social protection in the life of elderly people, whose trajectories in access are marked by fatigue, suffering, struggle, and slowness in responding to their demands. Among other conclusions, it was evinced that access to objective and direct information about the programs, services and benefits constitutes a central and strategic aspect in the defense of social rights towards human emancipation